Genese og diegese - et problem i den almene narratologi - Brandt, Per Aage (Religionsvidenskabeligt Tidsskrift, 1989)
The author proposes a structural distinction between the petits récits and the grands récits (according to Lyotard), between binary and trivial narrativity, on one hand, and bifurcational and fatal narrativity, on the other: reversibility vs. irreversibility. The ontological implications of the two types are distinct, and philosophy should be aware of this categorical difference; narrative theology and “theo-semiotics” in general must do it, if the analysis is correct, as this development of actantial schematism makes it possible to represent, for the first time, a dynamic structure which could be called the geometry of religious meaning.